Prevalencia de trastornos temporomandibulares y factores asociados en estudiantes de una universidad privada de Lima-Perú - Zevallos-Cabrera, Patricia (2022)
Introduction: Temporomandibular disorders (TMDs) are musculoskeletal and neuromuscular alterations that affect the temporomandibular joint, masticatory muscles, and contiguous structures. A high prevalence of TMD has been reported in university students, and it may also be associated with neck pain and emotional disturbances. The objective is to determine the prevalence and factors associated with TMD in university students. M ethods: An analytical cross-sectional observational study was conducted. The population was university students who have completed in 2021, aged between 18 and 35 years. The Fonseca Simplified Anamnestic Index Questionnaire, DASS-21, Nordic Questionnaire, and general data questionnaire were used. Results: 378 university students were included in the study, 73.6 % had TMD and 59.8 % had cervical pain in the last 7 days. 55.6 %, 71.4 %, and 65.6 % presented stress, anxiety, and depression, respectively. A significant association was found between TMD and cervical pain in the last 7 days (RPa=1.28, CI95 % 1.11 to 1.47, p=0.001), with anxiety (RPa=1.24, CI95 % 1.02 to 1.52, p=0.033) and with female sex (RPa=1.18, CI95 % 1.02 to 1.37, p=0.025). On the contrary, no association was found between TTM and the stress and depression variables. Conclusion: 73.6 % of university students had TMD, and it was also shown that cervical pain in the last 7 days and anxiety were associated with TMD. No relationship was found between stress and depression with TMD.